From the Frankfurt greenbelt to the Regionalpark RheinMain: an institutional perspective on regional greenbelt governance. Issue 1 (2nd January 2021) - Macdonald, Sara; Monstadt, Jochen; Friendly, Abigail
ABSTRACT: Legally protected by its own constitution since 1991, the greenbelt (or 'GrünGürtel') forms a ring of greenspace around Frankfurt, Germany and has been considered an effective reaction to municipal development pressures. As a response to Frankfurt's embeddedness within a highly interconnected suburbanized region under extensive growth pressures, the Regionalpark RheinMain was established to upscale the greenbelt to the regional level. In this article, we explore the institutional complexities of upscaling a localized greenbelt to the regional scale in the Frankfurt Rhine-Main region, which is known for its fragmented institutional environment formed by numerous planning authorities and special purpose agencies with overlapping jurisdictions. Engaging with the literature on the governance of greenbelts from an institutional perspective, we analyse how the development of the Regionalpark RheinMain is shaped by horizontal, vertical and territorial coordination problems. We conclude that that the Regionalpark RheinMain is not appropriately institutionalized to serve as an effective regional greenbelt, resulting in localized initiatives and the delegation of greenbelt planning to municipalities.